Estudo dos mecanismos de ação de leveduras envolvidos no biocontrole de doenças de pós-colheita em citros - Ferraz, Luriany Pompeo [UNESP] (2014)
Because of the economic and social importance that citrus industry represent to the country, and in particular to the state of São Paulo, citrus plants can be affected by several pathogenic agents , acting alone or together , under favorable conditions may make limiting the production in some production areas. Among these pathogenic agents have more importance Penicillium digitatum, Penicillium italicum and Geotrichum candidum, responsible for diseases that occuring in the post - harvest citrus. The most effective method of controlling these diseases is by means of chemical control, but control alternatives are needed in order to reduce environmental and human health risks due to the indiscriminate use of fungicides. Among the alternative methods, biological control has emerged as one of the most promising for disease control. So the present study was to evaluate the mechanisms of action of 24 yeast isolates that have potential for control of sour rot and mold in citrus fruits. Our study suggests that multiple modes of action, as shown by the majority of yeast isolates tested, which showed production of hydrolytic enzymes (chitinase and β-1,3-glucanase), killer activity and inhibition of conidial germination of the pathogen were important for the potential control of Geotrichum candidum, Penicillium digitatum and P. italicum. All yeast isolates showed killer activity, indicating that this is the common mechanism adopted by the biocontrol isolates